Experimental Warming Does Not Change Fluctuating Asymmetry in Three Willow Species - Gavrikov, Dmitry E.; Zverev, Vitali; Kozlov, Mikhail V. (Wiley, 2026)
Fluctuating asymmetry (FA) is often proposed as an early warning indicator of subtle changes in plant functioning. Here, we tested whether leaf FA responds consistently to the alleviation of cold stress in three boreal willow species—Salix caprea, S. myrsinifolia and S. phylicifolia. We enclosed 10 naturally growing individuals of each species in open-top chambers at budburst and compared their leaf traits to those of unenclosed control plants after leaf development had ceased. All measurements were conducted blind to treatment. Willows in open-top chambers showed a 9% increase in specific leaf area, indicating that the 1°C–2°C warming within chambers affected leaf development. However, neither leaf length nor FA responded significantly to the warming treatment. FA also did not differ among species or individual plants, suggesting that it may reflect statistical noise rather than a reliable biological signal in this context. These findings add to growing concerns that many reported FA responses to environmental change may result from confirmation bias—an issue that can be mitigated by adopting blind measurement protocols.